The development of ACAP seabird bycatch indicators, data needs, methodological approaches and reporting requirements - Wolfaardt, Anton (2020)
The Agreement on the Conservation of Albatrosses and Petrels (ACAP) is a multilateral environmentalagreement that seeks to achieve and maintain a favourable conservation status for albatrosses andpetrels. The Agreement is currently ratified by 13 countries. In addition, a number of non-Party RangeStates and international organisations actively participate in the work of the Agreement. The Agreementprovides a framework for coordinating and undertaking international activity to mitigate known threatsto populations of affected species, including fisheries bycatch. In order to monitor and report on theperformance of the Agreement, a system of indicators following the Pressure-State-Responseframework is being developed and implemented by ACAP. The primary Pressure indicator for bycatchcomprises two linked components: (i) the seabird bycatch rate across each of the fisheries of memberParties, and (ii) the total number of birds killed (bycaught) per year of ACAP species (per species wherepossible). The Seabird Bycatch Working Group of ACAP is currently undertaking work to developguidelines on issues that need to be considered in estimating and reporting against these bycatchindicators and, considering the estimation methods currently in use, to propose guidance andrecommendations to achieve consistent reporting. This paper provides an outline of therecommendations and guidelines that have been developed to date. It is important to note that thisrepresents work in progress, and is presented here to help inform discussions regarding seabird bycatchestimation and reporting within the Western and Central Pacific Fisheries Commission (WCPFC) andother RFMOs.